Improving the symptoms of post-traumatic osteoarthritis by α2-macroglobulin-rich serum. (2nd November 2022) - Wang, Xiaohu; Li, Lu; Wei, Xiaochun; Li, Pengcui; Zhao, Yu; Zhao, Ruipeng; Duan, Zhiqing
ABSTRACT: Purpose: Altered joint loading by trauma induces joint degeneration, eventually leading to the generation of post-traumatic osteoarthritis (PTOA). Recent studies have shown that α2-macroglobulin (A2M) inhibits PTOA, induced by anterior cruciate ligament transection (ACLT), pathogenesis by regulating proinflammatory cytokines and matrix metalloproteinases. However, the application of A2M is limited due to high prices. Therefore, the aim of this study is to explore the novel preparation of A2M. Materials and Methods: The early change of A2M in synovial fluid and serum was measured by ELISA. Ultra-filtered centrifugation was performed to prepare α2-macroglobulin-rich serum (A2MRS). The bioactivity of A2M in A2MRS was detected by improved Ellis and Gollas-Galvan method. The effects of A2MRS on PTOA were observed using immunohistochemistry, safranine O staining, micro X-ray, fluorescence molecular tomography etc. Results: The concentration of A2M in PTOA group was significantly higher than that in Sham group in synovial fluid on the third day after ACLT in rat PTOA model. On the contrary, a significant downregulation of A2M levels in PTOA group was observed compared to the Sham group in serum at the seventh day after ACLT. Secondly, A2MRS was prepared successfully, and the concentration and bioactivity of A2M in A2MRS was significantly higher than that in serum. Lastly, A2MRS not only reduced notably the production of secondary cartilage ossification, type 10 collagen and matrix metalloproteinase 13, but also increased profoundly the generation of type 2 collagen, aggrecan, and chondrocytes' number. Conclusion: Our results indicate that A2MRS has protective effects on PTOA.